Racism against immigrants in Brazil: a critical analysis of employers' discourse - Antunes, Camila Veloso; Neto, Antonio Carvalho (Revista de Administração da UFSM, 2023)
Objective: This article investigates the discursive representations related to racism of Brazilian employers and human resource managers on hired immigrant workers. Theoretical framework: The socio-cognitive theory proposed by Van Dijk is presented together with studies on discursive representations of immigrants. Methodology: The qualitative research used semi-structured interviews with 12 employers in the cities of São Paulo, Belo Horizonte and Porto Alegre. Data analysis was based on critical discourse analysis (CDA), on Van Dijk's socio cognitive approach. Results: The research showed that the employers' discourse is based on the assumptions that the immigrant workers: i) are more efficient than Brazilians; ii) subject themselves to any kind of work; iii) are destined for unqualified and hard work; iv) threaten Brazilians (different cultural identities; different community values; may be criminals; are disease spreaders); and v) are an economic burden. The Brazilian employer´s discourse maintains and perpetuates all the characteristics of the racist ideology and makes it difficult for immigrants to enter the Brazilian labour market, forging domination practices that favour social inequality. Originality: This study contributes to broaden the CDA scope of analysis when investigating employers and immigrants. It also dialogues and contributes to the literature in Brazil on CDA by specifically adopting Van Dijk's socio cognitive approach instead of the more adopted Fairclough perspective.